Design and optimization of a 3‐coil resonance‐based wireless power transfer system for biomedical implants. (15th September 2014) - Yi, Ying; Buttner, Ulrich; Fan, Yiqiang; Foulds, Ian G.
Summary This paper presents a resonance‐based wireless power transfer system using a single layer of inductor coil windings, in a pancake configuration, in order to obtain a compact system for implantable electronic applications. We theoretically analyzed the system and characterized it by measuring its inductance, self‐resonant frequency, and quality factor Q. In our resonance‐based wireless power transfer prototype, we proposed a 3‐coil system, using two 15‐mm radius implantable coils, with a resonance frequency of 6.76 MHz. This system can effectively transfer power for a distance of up to 50 mm. Moreover, our proposed 3‐coil system can achieve a high Q‐factor and has a comparable power transfer efficiency (PTE) to previously reported works about 3‐coil and 4‐coil systems. The experimental PTE can achieve 82.4% at a separation distance of 20 mm and more than 10% PTE at a distance of 40 mm. Copyright © 2014 John Wiley & Sons, Ltd.